Positive electrode active material

By using lithium compound particle metal composites with specific structures as positive electrode active substances in lithium-ion secondary batteries, the problem of reducing structural stability and life retention rate of lithium-ion secondary batteries in high-temperature environments is solved, and the battery is high Energy density and long-life performance are suitable for high-demand applications such as electric vehicles.

CN119137765APending Publication Date: 2024-12-13SK ON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380032351.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-31
Filing Date
2023-03-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Lithium-ion secondary batteries have problems with reduced structural stability and life retention rates in high-temperature environments, especially in electric vehicle applications, with the increasing demand for high-energy density batteries, and existing positive electrode active substances are difficult to maintain excellent performance in high-temperature environments. .

Method used

The metal composite containing lithium compound particles with a specific structure is used as the positive electrode active substance. By controlling the proportion and doping degree of metal elements in the lithium compound particles, a positive electrode active substance layer with excellent structural stability and lifetime retention is formed. Build efficient battery cells and battery components.

Benefits of technology

It has achieved significant improvement in the structural stability and life retention rate of the battery in high temperature environments, ensuring the high energy density and long life performance of the battery, and is suitable for high-demand applications such as electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137765A_ABST
    Figure CN119137765A_ABST
Patent Text Reader

Abstract

The present invention can provide a positive electrode active material exhibiting excellent structural stability and life retention even in a high-temperature environment in which a battery is operating. Further, the present invention may provide a positive electrode including an active material layer including the positive electrode active material, and a battery cell including the positive electrode. Further, an object of the present invention is to provide a battery cell assembly comprising the battery cell. In addition, the present invention may provide an electrical device including one or more selected from the group consisting of the battery cell and a battery cell assembly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material. Specifically, the present invention relates to a positive electrode active material used in a lithium secondary battery. In addition, the present invention relates to an application of the positive electrode active material. Background Art

[0002] With the development of electronics, communications and aerospace industries, the demand for secondary batteries as energy sources is rapidly increasing. In particular, with the emphasis on the importance of global environmental protection policies, the electric vehicle market is growing rapidly, and research and development of secondary batteries are being actively carried out at home and abroad.

[0003] In recent years, the demand for high energy density batteries for electric vehicles (EVs) is increasing, and the development of secondary batteries using high-nickel (High-Ni)-based positive electrodes is necessary. However, lithium-ion secondary batteries have problems with reduced structural stability and life retention in high-temperature environments, so there is still a need for positive electrode active materials that can solve this problem.

[0004] [Prior art literature]

[0005] (Patent Document 1) Korean Patent Publication No. 10-2022-0150693 (Invention Title: High-voltage battery module with excellent cooling efficiency)

[0006] (Patent Document 2) Korean Patent Publication No. 10-2022-0142853 (Invention Title: Battery Pack and Method of Manufacturing the Same) Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] An object of the present invention is to provide a positive electrode active material that exhibits excellent structural stability and life retention rate even in a high-temperature environment in which a battery is operated.

[0009] In addition, the present invention aims to provide a positive electrode including an active material layer containing the positive electrode active material, and to provide a battery cell including the positive electrode. In addition, the present invention aims to provide a battery cell assembly including the battery cell. In addition, the present invention aims to provide an electrical device including one or more selected from the battery cell and the battery cell assembly.

[0010] (II) Technical solution

[0011] A positive electrode active material according to an example of the present invention may include a metal composite 10 including lithium compound particles 11 represented by the following structural formula 1. In addition, R of the positive electrode active material according to the following formula A A It can be in the range of 2 or more to 30 or less.

[0012] [Structural Formula 1]

[0013] Li x Ni a Co b Mn c M 1 d M 2 e O 2+y

[0014] In the structural formula 1, it can be 0.95≤x≤1.10, 0.75≤a≤1, 0 <b≤0.2,0<c≤0.2,0<d≤0.15,0<e≤0.1,-0.5≤y≤0.1,M 1 It can be the first metal element, M 2 It may be a second metal element, the first metal element may include one or more selected from Al, Ti, Zr, Sb and Nb, and the second metal element may include one or more selected from Sr, Mg, Ba, Y and Ce. In another example, the second metal element may include Sr.

[0015] [Formula A]

[0016] R A =W Co / W M1

[0017] In formula A, W Co is the weight % of cobalt relative to the total weight of the metal composite 10, W M1 is the weight % of the first metal element relative to the total weight of the metal composite 10 .

[0018] According to one example of the present invention, the positive electrode active material has R according to the following formula B: B It can be in the range of 1 or more and 20 or less.

[0019] [Formula B]

[0020] R B =W Mn / W M1

[0021] In formula B, W Mn is the weight % of manganese relative to the total weight of the metal composite, W M1is the weight % of the first metal element relative to the total weight of the metal composite.

[0022] According to one example of the present invention, the positive electrode active material has R according to the following formula C: C It can be in the range of 30 or more and 500 or less.

[0023] [Formula C]

[0024] R C =W Ni / W M1

[0025] In formula C, W Ni is the weight % of nickel relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

[0026] In the positive electrode active material according to an example of the present invention, the metal composite 10 may include an extra-particle region 12 , and the extra-particle region 12 may include one or more selected from oxides, sulfides, oxysulfides, oxyfluorides, and hydrates of the first metal element.

[0027] In the positive electrode active material according to one example of the present invention, the lithium compound particles 11 may include the first metal element in a range of 0.001 to 0.1 mole relative to 1 mole of total lithium elements.

[0028] In the positive active material according to one example of the present invention, the lithium compound particles 11 may include the second metal element in a range of 0.0001 to 0.05 moles relative to 1 mole of the total lithium element.

[0029] In the positive electrode active material according to one example of the present invention, the first metal element in the lithium compound particles 11 may include Al, and may further include one or more selected from Ti, Zr, Sb, and Nb.

[0030] According to one example of the present invention, the positive electrode active material has R according to the following formula P: P It can be in the range of 0.1 to 10000.

[0031] [Formula P]

[0032] R P =N Al / N M1

[0033] In formula P, N Al is the mole % of Al relative to the total moles of the metal composite 10, N M1It is the total mole % of Ti, Zr, Sb and Nb relative to the total mole number of the metal composite 10.

[0034] In the positive electrode active material according to an example of the present invention, the first metal element in the lithium compound particles 11 may include Al and Ti. According to the following formula Q, R Q It can be in the range of 1000 to 10000.

[0035] [Formula Q]

[0036] R Q =N Al / N Ti

[0037] In formula Q, N Al is the mole % of Al relative to the total moles of the metal composite 10, N Ti It is the mole % of Ti relative to the total moles of the metal composite 10.

[0038] In the positive electrode active material according to an example of the present invention, the first metal element in the lithium compound particles 11 may include Al and Zr. According to the following formula R R Can be in the range of 0.1 to 50.

[0039] In the positive electrode active material according to an example of the present invention, the first metal element in the lithium compound particles 11 may include Al and Zr. According to the following formula R R Can be in the range of 0.1 to 50.

[0040] [Formula R]

[0041] R R =N Al / N Zr

[0042] In formula R, N Al is the mole % of Al relative to the total moles of the metal composite 10, N Zr It is the mole % of Zr relative to the total moles of the metal composite 10.

[0043] In the positive electrode active material according to one example of the present invention, R S Can be in the range of 1 to 100.

[0044] [Formula S]

[0045] R S =N Al / N Sb

[0046] In formula S, NAl is the mole % of Al relative to the total moles of the metal composite 10, N Sb It is the mole % of Sb relative to the total moles of the metal composite 10.

[0047] In the positive electrode active material according to an example of the present invention, the first metal element in the lithium compound particles 11 may include Al and Nb. According to the following formula T, R T Can be in the range of 1 to 50.

[0048] [Formula T]

[0049] R T =N Al / N Nb

[0050] In formula T, N Al is the mole % of Al relative to the total moles of the metal composite 10, N Nb It is the mole % of Nb relative to the total moles of the metal composite 10.

[0051] A positive electrode according to an example of the present invention may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer may include a positive electrode active material according to an example of the present invention.

[0052] A battery cell 1 according to an example of the present invention may include an electrode assembly and an electrolyte, wherein the electrode assembly may include a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, wherein the positive electrode may include a positive electrode collector and a positive electrode active material layer disposed on at least one side of the positive electrode collector, wherein the positive electrode active material layer may contain the positive electrode active material.

[0053] A battery cell assembly according to an example of the present invention may include more than one battery cell 1 , and at least one of the battery cells 1 may include the battery cell 1 according to an example of the present invention.

[0054] An electrical device according to an example of the present invention may include one or more selected from one or more battery cells 1 and one or more battery cell assemblies, at least one of the battery cells 1 may include a battery cell 1 according to an example of the present invention, and at least one of the battery cell assemblies may include a battery cell assembly according to an example of the present invention.

[0055] (III) Beneficial effects

[0056] The present invention can provide a positive electrode active material that exhibits excellent structural stability and life retention rate even in a high-temperature environment in which a battery is operated.

[0057] In addition, the present invention may provide a positive electrode including an active material layer containing the positive electrode active material, and may provide a battery cell including the positive electrode. In addition, an object of the present invention is to provide a battery cell assembly including the battery cell. In addition, the present invention may provide an electrical device including one or more selected from the battery cell and the battery cell assembly. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 is a diagram showing a metal composite according to one example of the present invention.

[0059] Figure 2 is a diagram showing the structure of a battery cell according to one example of the present invention.

[0060] Figure 3 is a diagram showing a structure of a battery module according to one example of the present invention.

[0061] Figure 4 is a diagram showing a structure of a battery pack according to one example of the present invention. DETAILED DESCRIPTION

[0062] The description of the structure or function of the embodiment disclosed in the present invention is merely exemplified for the purpose of illustrating the embodiment according to the technical idea of ​​the present invention. In addition, in addition to the embodiment disclosed in the present invention, the embodiment according to the technical idea of ​​the present invention can be implemented in various forms. In addition, the technical idea of ​​the present invention should not be interpreted as being limited to the embodiment described in the present invention.

[0063] Among the physical properties mentioned in the present invention, when the measurement temperature has an effect on the physical properties, unless otherwise specified, the physical properties are physical properties measured at normal temperature and pressure.

[0064] The term normal temperature used in the present invention may refer to a natural temperature that is not heated or cooled, for example, any temperature within the range of 10-30° C., for example, a temperature of about 15° C. or more, about 18° C. or more, about 20° C. or more, about 23° C. or more, about 27° C. or less, or 25° C. In the present invention, unless otherwise specifically provided, the unit of temperature is Celsius (° C.).

[0065] Among the physical properties mentioned in the present invention, when the measuring pressure has an effect on the physical properties, unless otherwise specified, the physical properties are the physical properties measured under normal pressure.

[0066] The term normal pressure used in the present invention refers to natural pressure without being pressurized or reduced, and generally, the gas pressure within the range of about 700 mmHg to 800 mmHg is referred to as normal pressure.

[0067] The term a to b used in the present invention means including a and b and being within the range between a and b. For example, comprising a to b parts by weight has the same meaning as being within the range comprising a to b parts by weight.

[0068] In the present invention, a battery may be used in the same meaning as a cell, and the battery or cell may be a general term for a battery cell 1 as a unit thereof, a battery module 2 including the battery cell, or a battery pack 3.

[0069] The present invention can provide a positive electrode active material that shows excellent structural stability and life retention rate even in a high temperature environment in which the battery operates. In addition, the present invention can provide a positive electrode including an active material layer containing the positive electrode active material, and can provide a battery cell 1 including the positive electrode. In addition, the object of the present invention is to provide a battery cell assembly including the battery cell 1. In addition, the present invention can provide an electrical device including one or more selected from the battery cell 1 and the battery cell assembly.

[0070] The term battery cell assembly used in the present invention may be a term including a battery module 2 and a battery pack 3. That is, the battery cell assembly may be a battery module 2 including a battery cell 1, and may be a battery pack 3 including one or more selected from the battery cell 1 and the battery module 2.

[0071] In the present invention, the battery cell 1, the battery module 2 and the battery pack 3 can be respectively referred to as Figures 2 to 4 .

[0072] The structure of the battery cell 1 according to an example of the present invention may be known. The structure of the battery cell 1 may be referred to, for example, Figure 2 The battery cell 1 may include an electrode assembly and an electrolyte 1d. Figure 2 , the electrode assembly may include a positive electrode 1a, a negative electrode 1b and a separator 1c. Figure 2 The battery cell 1 may have a structure including a positive electrode 1a and a negative electrode 1b with a separator 1c interposed therebetween. In addition, the battery cell 1 may have a structure in which an electrolyte 1d is filled in a space sealed by an exterior material 1e.

[0073] The positive electrode (cathode) 1a refers to a reduction electrode where an electron transport material receives electrons when the battery cell 1 is discharged. The positive electrode 1a may include a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer may be formed by a positive electrode slurry composition. In addition, the positive electrode active material layer and the positive electrode slurry composition may contain a positive electrode active material. The positive electrode active material may include the metal composite 10 described below according to an example of the present invention. In addition to the above-mentioned metal composite, the positive electrode active material may further include additional active materials that can be applied to the positive electrode in the art. The type of the additional active material is not particularly limited, but for example, it can be exemplified: layered compounds such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2) or compounds substituted by one or more transition metals; lithium iron oxides such as LiFe3O4; chemical formula Li 1+c1 Mn 2-c1 Lithium manganese oxides such as LiMnO4 (0≤c1≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 or Cu2V2O7; 1-c2 M c2 Ni-site lithium nickel oxide represented by O2 (wherein M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); 2-c3 M c3 Lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is at least one selected from Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from Fe, Co, Ni, Cu and Zn); lithium nickel cobalt manganese (NCM) composite oxides, lithium nickel cobalt manganese aluminum (NCMA) composite oxides and LiMn2O4 in which part of the Li in the chemical formula is substituted by alkaline earth metal ions, etc.

[0074] The metal composite 10 according to an example of the present invention may be one of lithium nickel cobalt manganese (NCM) composite oxides. In addition, the metal composite may be a metal composite in which a metal element is further doped in the lithium nickel cobalt manganese composite oxide.

[0075] By controlling the type of metal element doped in the metal composite 10 according to one example of the present invention and the content or quantity ratio of the doped metal element, a positive electrode active material showing excellent structural stability and life retention rate even in a high temperature environment of battery operation can be provided.

[0076] The negative electrode (anode) 1b refers to an oxidation electrode where an electron transport material transports electrons when the battery cell 1 is discharged. The negative electrode 1b may include a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer may be formed by a negative electrode slurry composition. In addition, the negative electrode active material layer and the negative electrode slurry composition may contain a negative electrode active material. The type of the negative electrode active material is not particularly limited, but compounds that can reversibly intercalate and deintercalate lithium can be used, for example. As specific examples, carbon-based materials such as graphite (artificial graphite, natural graphite or graphitized carbon fiber) or amorphous carbon; metal-based compounds that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys or Al alloys; SiO β (0<β≤2), metal oxides that can be doped and dedoped with lithium, such as SnO2, vanadium oxide or lithium vanadium oxide; or Si-C composites or Sn-C composites, etc., containing the metal-based compounds and carbon-based materials, and any one of them or a mixture of two or more of them can be used. In addition, as the negative electrode active material, a metallic lithium film can be used. As the carbon material, low-crystalline carbon and high-crystalline carbon can be used. Representative examples of low-crystalline carbon include soft carbon and hard carbon. Examples of highly crystalline carbon include amorphous, flaky, spherical or fibrous natural graphite or artificial graphite, primary graphite (Kish graphite), pyrolytic carbon, mesophase pitch based carbon fiber, carbon microspheres (mesocarbon microbeads), mesophase pitch, and high temperature calcined carbon such as petroleum and coal-based coke (petroleum or coal tar pitch derived cokes).

[0077] The positive electrode 1a and the negative electrode 1b may include each active material layer formed by applying each slurry composition on each current collector and drying. As needed, the active material layer may be calendered after drying. The method for carrying out the coating is not particularly limited, and a known method may be used. Specifically, the method for carrying out the coating may use a method using a slit die, a blade coating method, a dip coating method, a reverse roll coating method, a forward roll coating method, a gravure coating method, an extrusion method or a brush coating method, etc. Considering the thickness after drying, the coating thickness of the slurry composition may be applied with an appropriate thickness, and according to the coating thickness, the above-mentioned known method may be appropriately selected for carrying out. In addition, the method for carrying out the calendering may be carried out by a calendering fixture, etc., according to a known method.

[0078] The current collector used in the positive electrode 1a is not particularly limited in type, size, shape, etc. as long as it does not cause chemical changes in the battery cell 1 and has conductivity. The positive electrode current collector 1a can be made of, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or a material obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, or silver.

[0079] The current collector used in the negative electrode 1b is not particularly limited in type, size, shape, etc. as long as it does not cause chemical changes in the battery cell 1 and has conductivity. The negative electrode current collector can be made of, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or a material obtained by surface-treating the surface of copper or stainless steel with carbon, nickel, titanium, silver, or an aluminum-cadmium alloy.

[0080] In addition, the current collector and the active material layer may have an appropriate thickness as required. Although not particularly limited, the current collector may have a thickness in the range of 1-500 μm, or may have a thickness in the range of 1-300 μm, or may have a thickness in the range of 1-100 μm, or may have a thickness in the range of 1-50 μm. In addition, although not particularly limited, the active material layer may have a thickness in the range of 1-500 μm, or may have a thickness in the range of 1-300 μm, or may have a thickness in the range of 1-100 μm, or may have a thickness in the range of 1-50 μm.

[0081] In addition, each active material layer of the positive electrode 1a and the negative electrode 1b may further include a binder. The binder used is not particularly limited as long as it is a binder used in the art. For example, the binder may be selected from polyvinylidene fluoride (PVDF), polyvinyl alcohol, styrene butadiene rubber (SBR), polyethylene oxide, carboxyl methylcellulose (CMC), cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinyl acetate copolymer (poly(ethylene-co-vinyl acetate) copolymer), and the like. At least one of acetate) and polyarylate.

[0082] In addition, each active material layer of the positive electrode 1a and the negative electrode 1b can further include a conductive material independently as needed. The conductive material is not particularly limited as long as it does not cause chemical changes in the battery cell and has conductivity. For example, the conductive material can use graphite such as natural graphite or artificial graphite; carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon blacks; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes (CNTs); metal powders such as fluorocarbon powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal composites such as titanium oxide; conductive materials such as polyphenyl derivatives, etc.

[0083] In addition, each active material layer of the positive electrode 1a and the negative electrode 1b may further include a thickener, a reinforcing material, a leveling agent, an electrolyte additive, etc. as needed. The types of these are not particularly limited as long as they are used in the art.

[0084] In addition, the slurry composition forming each active material layer of the positive electrode 1a and the negative electrode 1b may include the components contained in the above-mentioned active material layer. In addition, the slurry composition may further include a solvent independently of each other. Taking into account the desired performance, etc., the solvent can be appropriately set, and the solvent can be an aqueous solvent such as water (pure water or ultrapure water, etc.), an organic solvent, or a mixed solvent of two or more. For example, the solvent may be an organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, cyclopentane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, methyl propionate, alcohol or ethyl propionate, or an aqueous solvent such as water, but water is most preferred in consideration of the drying temperature or environmental influences.

[0085] In addition, the current collector may have fine concavoconvexities on the surface to further enhance the adhesion with each active material layer. For example, the current collector may be in the form of one or more selected from a film, a sheet, a foil, a net, a porous body, a foam and a non-woven fabric.

[0086] In addition, the separator 1c refers to a film that prevents the short circuit between the positive electrode 1a and the negative electrode 1b and allows the electron transport material to pass. As long as the separator is a separator commonly used in the present technical field, it can be used without particular restriction. In particular, the separator preferably has a low resistance to the ion migration of the electrolyte and has excellent wettability (wettability, wettability) of the electrolyte. Specifically, the separator can use a porous polymer film, such as a porous polymer film made of polyolefin-based polymers such as ethylene polymers, propylene polymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, the separator can use conventional porous non-woven fabrics, such as non-woven fabrics made of high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer substance can be used, and it can be optionally used with a single-layer structure or a multilayer structure.

[0087] In addition, the electrolyte 1d refers to a medium that causes the migration of electron transport substances so that the electrochemical reaction of the positive electrode 1a and the negative electrode 1b proceeds smoothly. The electrolyte can use commonly used organic liquid electrolytes, inorganic liquid electrolytes, gel-type polymer electrolytes, molten inorganic electrolytes, etc., but is not limited to these. In addition, Figure 2 1d shows a liquid electrolyte, but as mentioned above, a solid electrolyte such as a gel polymer electrolyte can also be used. Batteries using solid electrolytes are generally called solid batteries or all-solid batteries. In the case of a liquid electrolyte (electrolyte), it generally contains an organic solvent and a lithium salt.

[0088] The organic solvent can be used without particular limitation as long as it can act as a medium for the migration of ions involved in the electrochemical reaction of the battery cell. Specifically, the organic solvent can be ester-based solvents such as methylacetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; ether-based solvents such as dibutyl ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (EPC). carbonate, PC) and other carbonate-based solvents; alcohol-based solvents such as ethanol and isopropanol; nitriles such as R-CN (R is a linear, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, and may contain a double-bonded aromatic ring or an ether bond) and amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, the hydrocarbon group may be one or more selected from an alkyl, alkenyl or alkynyl group. In addition, the organic solvent is preferably a carbonate-based solvent, and more preferably a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate, etc.) having high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery monomer and a low-viscosity chain carbonate-based compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.).

[0089] The lithium salt can be used without particular limitation as long as it is a compound that can provide lithium ions. Specifically, the lithium salt can use LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. The concentration of the lithium salt is preferably used in the range of 0.1-2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and thus can exhibit excellent electrolyte performance, and lithium ions can be effectively migrated.

[0090] In addition to the components of the electrolyte, the electrolyte may further contain one or more additives for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity and increasing the discharge capacity of the battery, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glycol dimethyl ether (n-glyme), hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc.

[0091] In the above, the battery is classified into various categories according to the type of electron transport material. For example, when the electron transport material is lithium (Li, including ions), the battery is called a lithium ion battery.

[0092] In addition, the outer packaging material 1e can protect the positive electrode 1a, the negative electrode 1b and the separator 1c from external impact, and can prevent the electrolyte 1d from leaking to the outside. According to the shape of the outer packaging material 1e, the battery cell 1 can be divided into a prismatic, cylindrical or soft-pack type. In the present invention, the battery cell 1 can preferably be a soft-pack type.

[0093] The discharge capacity of the battery cell 1 according to an example of the present invention relative to the molar ratio of nickel can be 2.3 mAh / g or more, 2.31 mAh / g or more, or 2.32 mAh / g or more. When the discharge capacity relative to the molar ratio of nickel meets the above lower limit, it can be evaluated as having excellent physical properties. The higher the discharge capacity relative to the molar ratio of nickel, the better the physical properties, so the upper limit is not particularly limited, but for example, it can be 5 mAh / g or less or 3 mAh / g or less. The discharge capacity relative to the molar ratio of nickel can be measured according to the following <Measurement method of physical properties>.

[0094] The LCR of the battery cell 1 according to one example of the present invention is calculated according to the following formula: R (High temperature life retention rate) can be 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, 75% or more, 76% or more, 77% or more, 78% or more, 79% or more, or 80% or more. R When the above lower limit is met, it can be evaluated as having excellent life retention rate. The higher the high temperature life retention rate, the better the physical properties, so the upper limit is not particularly limited, but for example, it can be 100% or less or 99% or less. In addition, the high temperature can refer to a relatively high temperature compared to normal temperature, and can refer to about 40°C or more or 45°C or less, or 100°C or less, 80°C or less, or 60°C or less. According to the following formula CR L R (High-temperature life retention rate) can be specifically measured according to <Methods for measuring physical properties>.

[0095] [Formula CR]

[0096] L R =L2 / L1×100(%)

[0097] In the formula CR, L1 is the discharge capacity of the battery cell in the first cycle under the condition of maintaining 45°C, and L2 is the discharge capacity of the battery cell in the 500th cycle under the condition of maintaining 45°C, wherein 1 cycle is defined as charging to 4.2V at 45°C with a current of 0.5C and a CC-CV charging mode, and then discharging to 2.5V at a current of 0.5C after 0.05C.

[0098] The total amount of gas generated by the battery cell 1 according to one example of the present invention when charging and discharging for 500 cycles at 45°C can be 10 mL / g or less, 9.5 mL / g or less, 9 mL / g or less, 8.5 mL / g or less, 8 mL / g or less, 7.5 mL / g or less, 7 mL / g or less, 6.5 mL / g or less, 6 mL / g or less, 5.5 mL / g or less, 4 mL / g or less, 3.5 mL / g or less, or 3 mL / g or less. When the total amount of gas meets the above upper limit or less, it can be evaluated as having excellent performance in preventing gas generation. The lower the total amount of gas, the better the physical properties, so the lower limit is not particularly limited, but for example, it can be 0.1 mL / g or more or 0.5 mL / g or more. The total amount of gas can be measured according to the gas generation amount of the following <Measurement method of physical properties>.

[0099] The structure of the battery module 2 according to an example of the present invention may be known. Figure 3. Reference Figure 3 The battery module 2 may have a structure including a battery cell unit 2a, an upper shell 2b-2 and a lower shell 2b-1, a bus bar 2c, and an inner cover 2d-1 and an outer cover 2d-2. In addition, the structure related to the battery module 2 can refer to Patent Document 1.

[0100] The battery module 2 may refer to a structure in which one or more battery cells 1 are placed in a housing to protect them from external impact, heat, vibration, etc. The battery module 2 is different from an assembly of the battery cells 1 in that the battery module 2 has a structure in which one or more battery cells 1 are placed in a housing.

[0101] The battery cell unit 2a may include more than one battery cell 1. When there are multiple battery cells 1, the battery cells 1 may be electrically connected in series and / or in parallel. The battery cell unit 2a may be built into the space formed by the lower shell 2b-1 and the upper shell 2b-2. However, the method of building the battery cell unit 2a is not limited to Figure 3 .

[0102] In addition, the term "electrical connection" used in the present invention may mean a state in which a circuit is formed when the connected objects are connected by a connection method and current can flow to each of the connected objects. The connection method is not particularly limited as long as it can be electrically connected, but it may be direct contact between the connected objects or a wire through which current can flow, etc. The plurality of battery cells 1 may be electrically connected to each other by series connection, parallel connection, or a combination thereof.

[0103] In addition, the battery cell 1 may include a tab. The battery cell 1 may specifically include a positive tab extending from the positive electrode and a negative tab extending from the negative electrode. The tab may be a term covering the positive tab and the negative tab. The battery cell unit 2a has a structure in which the positive tab and the negative tab protrude respectively corresponding to the number of battery cells 1 included. The positive tab and the negative tab may be electrically combined with a bus bar 2c having a slit, respectively. Electrical combination may be achieved by inserting the positive tab and the negative tab into the slit of the bus bar 2c, respectively. In addition, the battery module 2 includes an internal cover 2d-1 and an external cover 2d-2 to cover the bus bar 2c and the battery cell unit 2a.

[0104] The structure of the battery pack 3 according to an example of the present invention may be known in the art. Figure 4 . Figure 4 3 is a diagram simply showing an exemplary structure of the battery pack 3. Figure 4The battery pack 3 is provided with one or more battery modules 2 and electronic components 3e, such as various control devices such as BMS, etc., mounted on a placement surface 3b formed inside the battery pack housing 3a. In addition, the structure related to the battery pack 3 can refer to Patent Document 2.

[0105] The battery pack 3 may include a structure including one or more selected from the battery cells 1 and the battery modules 2 and equipped with various control devices such as a battery management system (BMS) and a cooling device, as well as a protection system. The battery pack 3 may be composed of battery cells 1 instead of battery modules 2, in which case it may be referred to as a so-called module-free battery pack (cell to pack).

[0106] The battery pack 3 may include various configurations to ensure the structural rigidity of the battery pack housing 3a. The battery pack 3 may include a crossbeam 3d that spans the entire tray 3a-1 and protrudes from the tray 3a-1 of the battery pack housing 3a to connect the oppositely disposed side wall portions 3a-2 of the battery pack housing 3a. In addition, the battery pack 3 may be provided with a partition 3c that protrudes from the tray 3a-1 of the battery pack housing 3a in the form of connecting the crossbeam 3d and the side wall portion 3a-2.

[0107] An electrical device according to an example of the present invention may include one or more selected from the battery cell 1 and the battery cell assembly. The electrical device is a device that is operated by the power generated by the battery cell 200, etc. The electrical device may be, for example, a mobile phone, a household appliance, an electric car, a hybrid electric car, or an energy storage device (energy storage system (ESS)).

[0108] A positive electrode active material according to one example of the present invention may include a metal composite 10 containing lithium compound particles 11, which are lithium nickel-cobalt-manganese (NCM) compounds doped with a first metal element and a second metal element. The first metal element may include one or more selected from Al, Ti, Zr, Sb and Nb. In addition, the second metal element may include one or more selected from Sr, Mg, Ba, Y and Ce. In addition, in another example, the second metal element may include Sr. A metal composite 10 according to one example of the present invention includes lithium compound particles 11, which are lithium nickel-cobalt-manganese (NCM) compounds doped with a first metal element and a second metal element, and the doping degree of the first metal element and the second metal element is controlled, so that the desired effect of the present invention can be achieved.

[0109] The lithium compound particles 11 may contain nickel (Ni). The nickel may be a metal element related to the capacity of the lithium secondary battery. The higher the nickel content in the lithium compound particles 11, the higher the capacity and power of the lithium secondary battery can be. However, when the nickel content is excessively increased, there is a problem of reduced lifespan.

[0110] In addition, the lithium compound particles 11 may include manganese (Mn). When a high content of nickel is used to improve capacity and power, the manganese may be distributed throughout the lithium compound particles 11, thereby compensating for chemical instability and mechanical instability caused by the high content of nickel.

[0111] In addition, the lithium compound particles 11 may include cobalt (Co). The cobalt may improve the conductivity or resistance characteristics of the lithium secondary battery.

[0112] The positive electrode active material according to an example of the present invention may specifically include a metal composite 10 including lithium compound particles 11 represented by the following structural formula 1.

[0113] [Structural Formula 1]

[0114] Li x Ni a Co b Mn c M 1 d M 2 e O 2+y

[0115] In the structural formula 1, it can be 0.95≤x≤1.10, 0.75≤a≤1, 0 <b≤0.2,0<c≤0.2,0<d≤0.15,0<e≤0.1,-0.5≤y≤0.1,M 1 It can be the first metal element, M 2 It may be a second metal element. As described above, the first metal element may include one or more selected from Al, Ti, Zr, Sb and Nb. In addition, in the positive electrode active material, the second metal element may include one or more selected from Sr, Mg, Ba, Y and Ce. In another example, the second metal element may include Sr.

[0116] In structural formula 1, M 1 and M 2 Each of the metal elements may independently contain more than one metal element. 1 It can contain Al and Ti, M 2 Sr may be contained. Accordingly, the obtained structural formula 1 is Li x Ni a Co bMn c A1 d1 Ti d2 Sr e O 2+y In addition, in Structural Formula 1, d and e refer to the sum of the subscripts of all metal elements included. For example, in the above illustration, d may refer to d1+d2.

[0117] In the positive active material according to one example of the present invention, when the metal composite 10 includes the lithium compound particles 11 represented by the structural formula 1, excellent structural stability and life retention rate can be ensured even in a high temperature environment in which the battery operates.

[0118] Figure 1 is a diagram showing a metal composite 10 according to an example of the present invention. Figure 1 The metal composite 10 may include one or more lithium compound particles 11. The lithium compound particles 11 may be grains. In addition, the metal composite 10 may have a structure formed by the aggregation of one or more lithium compound particles 11. In the present invention, the lithium compound particles 11 may be referred to as primary particles, and the metal composite 10 may be referred to as secondary particles formed by the aggregation of the primary particles.

[0119] In addition, the metal composite 10 may be formed only of the lithium compound particles 11. In addition, the metal composite 10 may include the lithium compound particles 11 and the extra-particle regions 12 present between the lithium compound particles 11. The extra-particle regions 12 may be voids or may be filled with other substances. The extra-particle regions 12 may include grain boundaries.

[0120] In addition, byproducts may be included in the extra-particle region 12. The metal composite 10 may include byproducts generated by external air or moisture on the surface of the lithium compound particle 11 or the metal composite 10 itself. The byproducts may be distributed in the extra-particle region 12, and the byproducts may include one or more selected from oxides, sulfides, oxysulfides, oxyfluorides, and hydrates of metal elements. Due to the byproducts, a phase change (for example, a phase change caused by a reaction of nickel ions and an electrolyte) may occur in the surface layer of the metal composite 10 or the lithium compound particle 11, and the crystal structure may be denatured.

[0121] In addition, the extra-particle region 12 may include one or more selected from oxides, sulfides, oxysulfides, oxyfluorides and hydrates of metal elements doped in the lithium compound particles 11. The doped metal may be one or more selected from the first metal element and the second metal element.

[0122] In addition, the extra-particle region 12 may include one or more selected from oxides, sulfides, oxysulfides, oxyfluorides, and hydrates of a first metal element, which is one of the metal elements doped in the lithium compound particle 11 .

[0123] In the positive electrode active material according to one example of the present invention, the average particle size (D50) of the metal composite 10 may be in the range of 2-25 μm or 3-18 μm. The term average particle size used in the present invention refers to the D50 particle size, which may refer to the particle size measured by the MASTERSIZER3000 device of Malvern according to the ISO-13320 standard. Distilled water is used as a solvent for the measurement. Due to the measurement object dispersed in the solvent, the incident laser is scattered, and the intensity and directivity values ​​of the scattered laser vary according to the size of the measurement object, which is analyzed using the Mie theory, so that the D50 particle size can be obtained.

[0124] In the positive electrode active material according to one example of the present invention, the content of the first metal element in the lithium compound particles 11 may be 0.001 mol or more, 0.0011 mol or more, 0.0012 mol or more, 0.0013 mol or more, 0.0014 mol or more, 0.0015 mol or more, 0.0016 mol or more, 0.0017 mol or more, or 0.0018 mol or more, or 0.1 mol or less, 0.09 mol or less, 0.08 mol or less, 0.07 mol or less, 0.06 mol or less, 0.05 mol or less, 0.04 mol or less, or 0.03 mol or less. In addition, the content of the first metal element in the lithium compound particles 11 may be within a range formed by appropriately selecting the above upper and lower limits. The total lithium element refers to the total lithium element contained in the lithium compound particles 11.

[0125] In the positive electrode active material according to one example of the present invention, when the content of the first metal element in the lithium compound particles 11 is within the above range, excellent structural stability and life retention rate can be ensured even in a high temperature environment of battery operation.

[0126] In the positive electrode active material according to one example of the present invention, the content of the second metal element in the lithium compound particles 11 may be 0.0001 mol or more, 0.0002 mol or more, or 0.0003 mol or less, or 0.05 mol or less, 0.04 mol or less, or 0.03 mol or less relative to 1 mol of the total lithium element. In addition, the content of the second metal element in the lithium compound particles 11 may be within a range formed by appropriately selecting the above upper and lower limits. The total lithium element refers to the total lithium element contained in the lithium compound particles 11.

[0127] In the positive electrode active material according to one example of the present invention, when the content of the second metal element in the lithium compound particles 11 is within the above range, excellent structural stability and life retention rate can be ensured even in a high temperature environment of battery operation.

[0128] The total molar number of lithium metal in the lithium compound particles 11 and the molar number of the specific metal element when the total molar number of lithium metal is set to 1 mole can be obtained according to the following <Method for measuring physical properties>, specifically, by ICP-OES analysis.

[0129] In the positive electrode active material according to one example of the present invention, the first metal element may include Al in the lithium compound particles 11. In addition, the first metal element may include Al and may further include one or more selected from Ti, Zr, Sb and Nb.

[0130] When the first metal element in the lithium compound particles 11 includes Al, excellent structural stability and lifespan retention rate can be ensured even in a high temperature environment in which the battery operates.

[0131] According to one example of the present invention, the positive electrode active material has R according to the following formula A: A It may be 2 or more, 2.1 or more, 2.2 or more, 2.3 or more, 2.4 or more, 2.5 or more, 2.6 or more, 2.7 or more, 2.8 or more, 2.9 or more, or 3 or less, 29 or less, 28 or less, 27 or less, 26 or less, 25 or less, 24 or less, 23 or less, 22 or less, 21 or less, or 20 or less. In addition, R of the positive electrode active material according to the following formula A is A It can be within the range formed by appropriately selecting the above upper limit and lower limit.

[0132] [Formula A]

[0133] R A =W Co / W M1

[0134] In formula A, W Co is the weight % of cobalt relative to the total weight of the metal composite 10, W M1 is the weight % of the first metal element relative to the total weight of the metal composite 10 .

[0135] When the positive electrode active material according to one embodiment of the present invention has R according to the formula A A When the above range is satisfied, excellent structural stability and life retention rate can be ensured even in a high-temperature environment in which the battery operates.

[0136] The weight % of the first metal element relative to the total weight of the metal composite 10 and the weight % of cobalt (Co) relative to the total weight of the metal composite 10 can be obtained according to the following <Measurement Method of Physical Properties>. The weight % of each metal element can be obtained by ICP analysis.

[0137] The inductively coupled plasma (ICP) analysis method used in the present invention can utilize the following methods according to appropriate circumstances: inductively coupled plasma-optical emission spectrometer (ICP-OES), inductively coupled plasma-atomic emission spectrometer (ICP-AES), inductively coupled plasma-mass spectrometer (ICP-MS) or inductively coupled plasma-atomic absorption spectrometer (ICP-AAS). Considering the measurement object, it is preferred to use ICP-OES for analysis.

[0138] According to one example of the present invention, the positive electrode active material has R according to the following formula B: B It may be 1 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.7 or more, or 20 or less, 19.5 or less, 19 or less, 18.5 or less, or 18 or less. In addition, R of the positive electrode active material according to the following formula B is B It can be within the range formed by appropriately selecting the above upper limit and lower limit.

[0139] [Formula B]

[0140] R B =W Mn / W M1

[0141] In formula B, W Mn is the weight % of manganese relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

[0142] When the positive electrode active material according to one embodiment of the present invention has R according to the formula B B When the above range is satisfied, excellent structural stability and life retention rate can be ensured even in a high-temperature environment in which the battery operates.

[0143] The weight % of the first metal element relative to the total weight of the metal composite 10 and the weight % of manganese (Mn) relative to the total weight of the metal composite 10 can be obtained according to the following <Measurement Method of Physical Properties>. The weight % of each metal element can be obtained by ICP analysis.

[0144] According to one example of the present invention, the positive electrode active material has R according to the following formula C: C It may be 30 or more, 35 or more, 40 or more, 45 or more, or 50 or less, 450 or less, 400 or less, or 350 or less. In addition, R of the positive electrode active material according to the following formula C C It can be within the range formed by appropriately selecting the above upper limit and lower limit.

[0145] [Formula C]

[0146] R C =W Ni / W M1

[0147] In formula C, W Ni is the weight % of nickel relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

[0148] When the positive electrode active material according to one embodiment of the present invention has R according to the formula C C When the above range is satisfied, excellent structural stability and life retention rate can be ensured even in a high-temperature environment in which the battery operates.

[0149] The weight % of the first metal element relative to the total weight of the metal composite 10 and the weight % of nickel (Ni) relative to the total weight of the metal composite 10 can be obtained according to the following <Measurement Method of Physical Properties>. The weight % of each metal element can be obtained by ICP analysis.

[0150] According to one example of the present invention, the positive electrode active material has R according to the following formula P: P It may be 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, 1 or more, or 10000 or less, 9500 or less, 9000 or less, 8500 or less, or 8200 or less. In addition, the positive electrode active material has R according to the following formula P: P It can be within the range formed by appropriately selecting the above upper limit and lower limit.

[0151] [Formula P]

[0152] R P =N Al / N M1

[0153] In formula P, N Al is the mole % of Al relative to the total moles of the metal composite 10, N M1 It is the total mole % of Ti, Zr, Sb and Nb relative to the total mole number of the metal composite 10.

[0154] When the positive electrode active material according to one embodiment of the present invention is R according to the formula P P When the above range is satisfied, excellent structural stability and life retention rate can be ensured even in a high-temperature environment in which the battery operates.

[0155] In the positive electrode active material according to one example of the present invention, the first metal element in the lithium compound particles 11 may include Al and Ti. In this case, R of the positive electrode active material according to the following formula Q Q It may be 1000 or more, 1100 or more, 1200 or more, 1300 or more, 1400 or more, or 10000 or less, 9500 or less, 9000 or less, 8500 or less, or 8200 or less. In addition, R of the positive electrode active material according to the following formula Q Q It can be within the range formed by appropriately selecting the above upper limit and lower limit.

[0156] [Formula Q]

[0157] R Q =N Al / NTi

[0158] In formula Q, N Al is the mole % of Al relative to the total moles of the metal composite 10, N Ti It is the mole % of Ti relative to the total moles of the metal composite 10.

[0159] In the positive electrode active material according to one example of the present invention, when the lithium compound particles 11 contain Al and Ti as the first metal element and R Q When the above range is satisfied, excellent structural stability and life retention rate can be ensured even in a high-temperature environment in which the battery operates.

[0160] In the positive electrode active material according to one example of the present invention, the first metal element in the lithium compound particles 11 may include Al and Zr. In this case, R of the positive electrode active material according to the following formula R R It may be 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, 1 or more, 1.1 or more, or 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 15 or less, or 12 or less. In addition, the positive electrode active material has R according to the following formula R R It can be within the range formed by appropriately selecting the above upper limit and lower limit.

[0161] [Formula R]

[0162] R R =N Al / N Zr

[0163] In formula R, N Al is the mole % of Al relative to the total moles of the metal composite 10, N Zr It is the mole % of Zr relative to the total moles of the metal composite 10.

[0164] In the positive electrode active material according to one example of the present invention, when the lithium compound particles 11 contain Al and Zr as the first metal element and R of the formula R R When the above range is satisfied, excellent structural stability and life retention rate can be ensured even in a high-temperature environment in which the battery operates.

[0165] In the positive electrode active material according to one example of the present invention, the first metal element in the lithium compound particles 11 may include Al and Sb. In this case, R of the positive electrode active material according to the following formula S SIt may be 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, 11 or more, 12 or more, or 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, or 20 or less. In addition, the positive electrode active material has R according to the following formula S: S It can be within the range formed by appropriately selecting the above upper limit and lower limit.

[0166] [Formula S]

[0167] R S =N Al / N Sb

[0168] In formula S, N Al is the mole % of Al relative to the total moles of the metal composite 10, N Sb It is the mole % of Sb relative to the total moles of the metal composite 10.

[0169] In the positive electrode active material according to one example of the present invention, when the lithium compound particles 11 contain Al and Sb as the first metal element and R S When the above range is satisfied, excellent structural stability and life retention rate can be ensured even in a high-temperature environment in which the battery operates.

[0170] In the positive electrode active material according to one example of the present invention, the first metal element in the lithium compound particles 11 may include Al and Nb. In this case, R of the positive electrode active material according to the following formula T T It may be 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, or 6 or less, or 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 15 or less, or 10 or less. In addition, the positive electrode active material has R according to the following formula T: T It can be within the range formed by appropriately selecting the above upper limit and lower limit.

[0171] [Formula T]

[0172] R T =N Al / N Nb

[0173] In formula T, N Al is the mole % of Al relative to the total moles of the metal composite 10, N Nb It is the mole % of Nb relative to the total moles of the metal composite 10.

[0174] In the positive electrode active material according to one example of the present invention, when the lithium compound particles 11 contain Al and Nb as the first metal element and R according to the formula T T When the above range is satisfied, excellent structural stability and life retention rate can be ensured even in a high-temperature environment in which the battery operates.

[0175] The mol% of a specific metal element relative to the total mol number of the metal composite 10 can be obtained according to the following <Measurement method of physical properties>. The mol% of a specific metal element relative to the total mol number of the metal composite 10 can be obtained by ICP-OES analysis.

[0176] The method for preparing the metal composite 10 according to an example of the present invention may include a step of preparing a precursor of the metal composite using a dispersion including a nickel compound, a cobalt compound, and a manganese compound.

[0177] The nickel compound, cobalt compound and manganese compound may be materials for forming the lithium compound particles 11. The nickel compound may be nickel sulfate, etc., the cobalt compound may be cobalt sulfate, etc., and the manganese compound may be manganese sulfate, etc.

[0178] The term dispersion used in the present invention refers to a mixture in which a solute is dispersed and not dissolved in a specific solvent.

[0179] In the method for preparing the metal composite 10 according to an example of the present invention, the step of preparing the precursor of the metal composite may include the step of reacting the dispersion in an alkaline environment. The alkaline environment may be formed by an alkaline substance, and the pH measured at room temperature may be about 9 or more or 10 or more, or may be 12 or less or 11.5 or less. The alkaline substance may use a substance that has little physical or chemical effect on the dispersion, for example, an alkaline substance such as sodium hydroxide or potassium hydroxide may be used.

[0180] In addition, the method for preparing the metal composite 10 may include a step of calcining a mixture including the prepared precursor of the metal composite, a lithium compound, and one or more second compounds including a second metal element.

[0181] The lithium compound may be a material for forming the lithium compound particles 11. The lithium compound may be lithium hydroxide or the like. The second metal element may include one or more selected from Sr, Mg, Ba, Y, and Ce. In another example, the second metal element may include Sr. The second compound may be an oxide or hydroxide of the second metal element.

[0182] In addition, in the method for preparing the metal composite 10, at least one selected from the dispersion and the mixture may include at least one first compound including a first metal element. The first metal element may include at least one selected from Al, Ti, Zr, Sb, and Nb. The first compound may be an oxide or hydroxide of the first metal element.

[0183] In the method for preparing the metal composite 10 according to one example of the present invention, the step of calcining the mixture (calcining step) may include a temperature increasing step of increasing the temperature from room temperature to a final temperature in the range of 650-750° C. at a temperature increasing rate of 1-8° C. / min. The temperature increasing rate may be in the range of 1.5-7° C. / min, or may be in the range of 2-6° C. / min. In the method for preparing the metal composite 10, based on the above materials and the conditions of the calcining step, the desired metal composite 10 of the present invention may be obtained. In particular, when the temperature increasing rate in the calcining step is not within the above range, the desired metal composite 10 of the present invention cannot be obtained.

[0184] In the method for preparing the metal composite 10 according to one example of the present invention, the step of calcining the mixture (calcining step) may further include a step of performing a heat treatment within a range of 5 to 20 hours while maintaining the final temperature. When the heat treatment time is within the above range, the desired metal composite 10 of the present invention can be obtained.

[0185] In the method for preparing the metal composite 10 according to one example of the present invention, the step of calcining the mixture (calcining step) may be performed in an environment where oxygen (O2) passes. In addition, in the method for preparing the metal composite 10 according to one example of the present invention, in the step of calcining the mixture (calcining step), oxygen may pass at a flow rate in the range of 1-50 mL / min. As described above, when oxygen having a flow rate in a specific range is passed in the calcining step, the desired metal composite 10 of the present invention can be obtained.

[0186] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples. However, the following Examples and Comparative Examples are merely illustrative for describing the present invention in more detail, and the present invention is not limited to the following Examples and Comparative Examples.

[0187] 1. Preparation of Metal Complexes

[0188] Example 1.

[0189] NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to a reactor at a mole ratio of 93:3:3:0.5 (A:B:C:D). Distilled water was added to the reactor and dispersed to prepare a transition metal dispersion. The distilled water was bubbled with nitrogen (N2) for about 24 hours to remove dissolved oxygen inside and used.

[0190] In another reactor, the prepared transition metal dispersion, sodium hydroxide (NaOH) aqueous solution and ammonia water are added at an appropriate addition rate, the pH is adjusted to about 10.5, and a coprecipitation reaction is carried out while stirring at a constant speed. The temperature during the reaction is maintained at about 60°C, and the coprecipitation reaction is carried out for about 48 hours. After the coprecipitation reaction is completed, the Na + and SO4 2- Thereafter, the precipitate was dried in an oven at about 120° C. for about 10 hours to prepare a precursor of a metal composite.

[0191] Lithium hydroxide and the prepared precursor of the metal composite were added to a dry high-speed mixer at a molar ratio of 1.04:1 (lithium hydroxide: precursor of the metal composite). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of about 0.11 mol %. Thereafter, the additives are uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0192] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 680°C at a heating rate of 5°C / min in an environment where oxygen (O2) was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 680°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a Li-containing 1.04 Ni 0.93 Co 0.03 Mn 0.03 Al 0.01 Sr 0.0011 O 1.53 A metal complex of lithium compound particles having a chemical formula.

[0193] Example 2.

[0194] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4.6H2O (A), CoSO4.7H2O (B) and MnSO4.H2O (C) were added to the reactor at a molar ratio of 93:3:2 (A:B:C).

[0195] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 1.02:1:0.02 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 + N2), strontium hydroxide (Sr(OH)2) was added to the dry high-speed mixer at a ratio of about 0.11 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0196] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 690°C at a heating rate of 2°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 690°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a Li-containing 1.02 Ni 0.93 Co 0.03 Mn 0.02 Al 0.02 Sr 0.0011 O 1.52 A metal complex of lithium compound particles having a chemical formula.

[0197] Example 3.

[0198] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 95:3:2:0.09 (A:B:C:D).

[0199] Lithium hydroxide and the prepared precursor of the metal composite were added to a dry high-speed mixer at a molar ratio of 1.07:1 (lithium hydroxide: precursor of the metal composite). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of 0.11 mol%. In addition, further, relative to the total molar number (N) of all the metal elements contained in the precursor of the metal composite, the total molar number of all the metal elements contained in the precursor of the metal composite is added. T1 ), zirconium oxide (ZrO2) was added to the dry high-speed mixer at a ratio of about 0.164 mol %. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0200] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 690°C at a heating rate of 2°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 690°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a Li-containing 1.07 Ni 0.93 Co 0.03 Mn 0.02 Al 0.002 Zr 0.0016 Sr 0.0011 O 1.53 A metal complex of lithium compound particles having a chemical formula.

[0201] Example 4.

[0202] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 89:5:4:0.5 (A:B:C:D).

[0203] Lithium hydroxide and the prepared precursor of the metal composite were added to a dry high-speed mixer at a molar ratio of 1.01:1 (lithium hydroxide: precursor of the metal composite). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of about 0.17 mol %. Thereafter, the additives are uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0204] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 700°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 700°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a mixture containing Li 1.01 Ni 0.89 Co 0.05 Mn 0.04 Al 0.010 Sr 0.0017 O 1.51 A metal complex of lithium compound particles having a chemical formula.

[0205] Example 5.

[0206] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4.6H2O (A), CoSO4.7H2O (B) and MnSO4.H2O (C) were added to the reactor at a molar ratio of 89:5:4 (A:B:C).

[0207] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 1.03:1:0.006 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 + N2), strontium hydroxide (Sr(OH)2) was added to the dry high-speed mixer at a ratio of about 0.11 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0208] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 710°C at a heating rate of 2°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 710°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a Li-containing 1.03 Ni 0.89 Co 0.05 Mn 0.05 Al 0.004 Sr 0.0011 O 1.52 A metal complex of lithium compound particles having a chemical formula.

[0209] Example 6.

[0210] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4.6H2O (A), CoSO4.7H2O (B) and MnSO4.H2O (C) were added to the reactor at a molar ratio of 89:5:5 (A:B:C).

[0211] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 1.03:1:0.012 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 + N2), strontium hydroxide (Sr(OH)2) was added to the dry high-speed mixer at a ratio of about 0.17 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0212] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 710°C at a heating rate of 2°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 710°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a Li-containing 1.03 Ni 0.89 Co 0.05 Mn 0.05 Al 0.009 Sr 0.0017 O 1.52 A metal complex of lithium compound particles having a chemical formula.

[0213] Example 7.

[0214] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 89:5:4:0.375 (A:B:C:D).

[0215] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 1.01:1:0.0075 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 + N2), strontium hydroxide (Sr(OH)2) was added to the dry high-speed mixer at a ratio of about 0.17 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0216] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 700°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 700°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a mixture containing Li 1.01 Ni 0.89 Co 0.05 Mn 0.04 Al 0.0144 Sr 0.0017 O 1.51 A metal complex of lithium compound particles having a chemical formula.

[0217] Example 8.

[0218] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 89:5:4:0.273 (A:B:C:D).

[0219] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 1.01:1:0.0055 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1+ N2), strontium hydroxide (Sr(OH)2) was added to the dry high-speed mixer at a ratio of 0.22 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0220] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 700°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 700°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a mixture containing Li 1.01 Ni 0.94 Co 0.05 Mn 0.04 Al 0.0104 Sr 0.0022 O 1.51 A metal complex of lithium compound particles having a chemical formula.

[0221] Example 9.

[0222] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 88:5:4:1.05 (A:B:C:D).

[0223] Lithium hydroxide and the prepared precursor of the metal composite were added to a dry high-speed mixer at a molar ratio of 0.97:1 (lithium hydroxide: precursor of the metal composite). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of 0.27 mol%. In addition, further, relative to the total molar number (N) of all the metal elements contained in the precursor of the metal composite, the total molar number of all the metal elements contained in the precursor of the metal composite is added. T1 ), zirconium oxide (ZrO2) was added to the dry high-speed mixer at a ratio of 0.211 mol %. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0224] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 700°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 700°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a mixture containing Li 0.97 Ni 0.88 Co 0.05 Mn 0.04 Al 0.020 Zr 0.0021 Sr 0.0027 O 1.5 A metal complex of lithium compound particles having a chemical formula.

[0225] Example 10.

[0226] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 88:5:3:1.4 (A:B:C:D).

[0227] Lithium hydroxide and the prepared precursor of the metal composite were added to a dry high-speed mixer at a molar ratio of 1.05:1 (lithium hydroxide: precursor of the metal composite). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of about 0.34 mol%. In addition, further, relative to the total molar number (N) of all the metal elements contained in the precursor of the metal composite, T1 ), antimony hydroxide (Sb(OH)2) was added to the dry high-speed mixer at a ratio of 0.20 mol %. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0228] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 700°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 700°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a mixture containing Li 1.05 Ni 0.88 Co 0.05 Mn 0.03 Al0.024 Sb 0.0020 Sr 0.0034 O 1.53 A metal complex of lithium compound particles having a chemical formula.

[0229] Example 11.

[0230] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 89:5:4:0.55 (A:B:C:D).

[0231] Lithium hydroxide and the prepared precursor of the metal composite were added to a dry high-speed mixer at a molar ratio of 1.03:1 (lithium hydroxide: precursor of the metal composite). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of about 0.22 mol%. In addition, further, relative to the total molar number (N) of all the metal elements contained in the precursor of the metal composite, the total molar number of all the metal elements contained in the precursor of the metal composite is added. T1 ), titanium dioxide (TiO2) was added to the dry high-speed mixer at a ratio of 0.0007 mol %. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0232] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 700°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 700°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a mixture containing Li 1.03 Ni 0.89 Co 0.05 Mn 0.04 Al 0.0094 Ti 0.000007 Sr 0.022 O 1.52 A metal complex of lithium compound particles having a chemical formula.

[0233] Example 12.

[0234] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 81:8:9:0.543 (A:B:C:D).

[0235] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 0.99:1:0.0109 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 + N2), strontium hydroxide (Sr(OH)2) was added to the dry high-speed mixer at a ratio of about 0.52 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0236] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 730°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 730°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a Li-containing 0.99 Ni 0.81 Co 0.08 Mn 0.09 Al 0.0146 Sr 0.0052 O 1.5 A metal complex of lithium compound particles having a chemical formula.

[0237] Example 13.

[0238] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 81:8:9:0.21 (A:B:C:D).

[0239] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 1.02:1:0.00105 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 +N2), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of about 0.49 mol%. In addition, further, relative to the total molar number (N T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 + N2), zirconium oxide (ZrO2) was added to the dry high-speed mixer at a ratio of about 0.22 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0240] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 730°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 730°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a Li-containing 1.02 Ni 0.81 Co 0.08 Mn 0.09 Al 0.0057 Zr 0.0022 Sr 0.0049 O 1.51 A metal complex of lithium compound particles having a chemical formula.

[0241] Example 14.

[0242] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 81:8:9:0.185 (A:B:C:D).

[0243] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 1:1:0.0037 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 +N2), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of about 0.47 mol%. In addition, further, relative to the total molar number (N T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 +N2), niobium hydroxide (Nb(OH)3) was added to the dry high-speed mixer at a ratio of about 0.108 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0244] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 730°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 730°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a LiNi 0.81 Co 0.08 Mn 0.09 Al 0.047 Nb 0.00108 Sr 0.0047 O 1.5 A metal complex of lithium compound particles having a chemical formula.

[0245] Example 15.

[0246] The precursor of the metal composite was prepared by the same method as in Example 1, except that NiSO4·6H2O (A), CoSO4·7H2O (B), MnSO4·H2O (C) and Al2(SO4)3 (D) were added to the reactor in a molar ratio of 79:9:9:0.8125 (A:B:C:D).

[0247] Lithium hydroxide, the prepared precursor of the metal composite, and aluminum hydroxide (Al(OH)3) were added to a dry high-speed mixer at a molar ratio of 1:1:0.01625 (lithium hydroxide: precursor of the metal composite: aluminum hydroxide). In addition, the total molar number (N) of all the metal elements contained in the precursor of the metal composite was added together. T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 +N2), strontium hydroxide (Sr(OH)2) is added to the dry high-speed mixer at a ratio of about 0.77 mol%. In addition, further, relative to the total molar number (N T1 ) plus the total number of moles of aluminum in the aluminum hydroxide (N2) (N T1 +N2), titanium dioxide (TiO2) was added to the dry high-speed mixer at a ratio of about 0.0004 mol%. Thereafter, the additives were uniformly mixed with the dry high-speed mixer for about 5 minutes to prepare a mixture.

[0248] The mixture was placed in a calcining furnace. The mixture placed in the calcining furnace was heated from room temperature to 730°C at a heating rate of 5°C / min in an environment where oxygen was passed at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 730°C. After the heat treatment (calcination) was completed, the heat-treated mixture was naturally cooled to room temperature, and pulverized and classified to prepare a LiNi 0.79 Co 0.09 Mn 0.09 Al 0.0203 Ti 0.000004 Sr 0.0077 O 1.5 A metal complex of lithium compound particles having a chemical formula.

[0249] Example 16.

[0250] The metal composite was prepared by the same method as in Example 4, except that when preparing the mixture, the total mole number (N) of all the metal elements contained in the precursor of the metal composite was added. T1 ), strontium hydroxide (Sr(OH)2) is mixed at a ratio of about 0.03 mol%. The metal composite prepared here comprises Li 1.01 Ni 0.89 Co 0.05 Mn 0.04 Al 0.008 Sr 0.0003 O 1.5Lithium compound particles with the chemical formula of .

[0251] Example 17.

[0252] The metal composite was prepared by the same method as in Example 4, except that when preparing the mixture, the total mole number (N) of all the metal elements contained in the precursor of the metal composite was added. T1 ), strontium hydroxide (Sr(OH)2) is mixed at a ratio of about 0.11 mol%. The metal composite prepared here comprises Li 1.01 Ni 0.89 Co 0.05 Mn 0.04 Al 0.009 Sr 0.0011 O 1.5 Lithium compound particles with the chemical formula of .

[0253] Example 18.

[0254] The metal composite was prepared by the same method as in Example 4, except that when preparing the mixture, the total mole number (N) of all the metal elements contained in the precursor of the metal composite was added. T1 ), strontium hydroxide (Sr(OH)2) is mixed at a ratio of about 0.21 mol%. The metal composite prepared here comprises Li 1.01 Ni 0.89 Co 0.05 Mn 0.04 Al 0.008 Sr 0.0021 O 1.5 Lithium compound particles with the chemical formula of .

[0255] Comparative Example 1.

[0256] The precursor of the metal composite was prepared by the same method as in Example 5. In addition, a mixture was prepared by the same method as in Example 5.

[0257] The mixture is placed in a calcining furnace. The mixture placed in the calcining furnace is heated from room temperature to 690°C at a heating rate of 10°C / min in an environment where oxygen flows at a flow rate of 10 mL / min, and heat-treated (calcined) for 10 hours while being maintained at 690°C. After the heat treatment (calcination) is completed, the heat-treated mixture is naturally cooled to room temperature, and pulverized and classified to prepare a LiNi 0.9 Co 0.05 Mn 0.05 Al 0.0004 Sr 0.0001 O 1.5A metal complex of lithium compound particles having a chemical formula.

[0258] Comparative Example 2.

[0259] The metal composite was prepared by the same method as in Comparative Example 1, except that when preparing the mixture, the total mole number (N) of all the metal elements contained in the precursor of the metal composite was added. T1 ), titanium dioxide (TiO2) is further mixed into the dry high-speed mixer at a ratio of about 0.0007 mol%. The metal composite prepared here comprises LiNi 0.9 Co 0.05 Mn 0.05 Al 0.0004 Sr 0.0001 Ti 0.0000012 O 1.5 Lithium compound particles with the chemical formula of .

[0260] 2. Manufacturing of battery cells

[0261] The metal composite (P1), conductive material (P2) and binder (P3) prepared in the embodiment and comparative example are mixed in a weight ratio of 95:3:2 (P1:P2:P3), and an appropriate amount of solvent is added to prepare a positive electrode slurry composition. Wherein, the conductive material (P2) uses acetylene carbon black (Denka black), and the binder (P3) uses polyvinylidene fluoride (PVDF). In addition, the solvent uses N-methyl-2-pyrrolidone (NMP). The positive electrode slurry composition is coated on one side of an aluminum foil (foil) having a thickness of about 12 μm and dried and rolled to produce a positive electrode having an electrode density of 3.5 g / cubic centimeter (cc) or more. Natural graphite (N1), a conductive material (N2), a binder (N3) and a thickener (N4) are mixed in a weight ratio of 94:4:1:1 (N1:N2:N3:N4), and an appropriate amount of solvent is added to prepare a negative electrode slurry composition. Among them, the conductive material (N2) uses acetylene black, and the binder (N3) uses styrene butadiene rubber (SBR). In addition, the thickener (N4) uses carboxymethyl cellulose (CMC), and the solvent uses pure water (deionized water). The negative electrode slurry composition is coated on one side of a copper foil having a thickness of about 8 μm and dried and rolled to manufacture a negative electrode.

[0262] The positive electrode and negative electrode prepared as described above are respectively subjected to a prescribed cutting process and stacked, and then a polyethylene material separator with a thickness of about 25 μm is arranged between the positive electrode and the negative electrode to manufacture an electrode assembly. Thereafter, the electrode assembly is placed in a soft bag, and an electrolyte is injected and sealed, and the electrode assembly is immersed in the electrolyte for more than 12 hours to manufacture a battery cell.

[0263] The electrolyte uses an electrolyte in which an additive is added to a mixed solvent in which 1M LiPF6 is dissolved, and the additive is an additive mixed with vinylene carbonate (VC), 1,3-propenesultone (PRS) and lithium bis(oxalato)borate (LiBOB) in a weight ratio of 1:0.5:0.5 (VC:PRS:LiBOB). The mixed solvent uses a solvent mixed with ethylene carbonate (EC), ethylmethyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of 30:40:30 (EC:EMC:DEC).

[0264] <Measurement Methods of Physical Properties>

[0265] The physical properties mentioned in the present invention can be measured as follows, and the physical properties in the following Examples and Comparative Examples were measured as follows.

[0266] 1. Content of each metal element in the metal complex

[0267] A weighed sample of 0.1 g of the metal complex is placed in a vial and about 1 mL of nitric acid is added. After that, a small amount of acidic substance (nitric acid: sulfuric acid = 3:1 (w / w) mixed solution) is added to the vial and heated on a hot plate to dissolve the sample. When the sample is completely dissolved and transparent, grade 3 ultrapure water is added to make the total volume 10 mL to prepare an analytical sample. For the analytical sample, the content of each metal element in the metal complex (unit: mass ppm) is measured by inductively coupled plasma-optical emission spectrometry (ICP-OES), and the analysis conditions are as follows. Based on the content of each metal element measured according to the analysis, the content ratio between the metal elements or the metal complex and the structural formula of the lithium compound particles contained in the metal complex can be obtained.

[0268] [ICP-OES analysis conditions]

[0269] RF power: 1300W

[0270] Torch Height: 15.0mm

[0271] Plasma Gas Flow: 15.00L / min

[0272] Sample Gas Flow: 0.8L / min

[0273] Aux. Gas Flow: 0.2L / min

[0274] Pump Speed: 1.5mL / min

[0275] Internal Standard: Yttrium (Y) or Scandium (Sc)

[0276] 2. Discharge capacity in terms of molar ratio % relative to nickel

[0277] At 25°C, a constant current was applied at a current rate of 1.5C until the voltage of the battery cell reached 4.2V. Afterwards, at the same temperature as above, the battery was discharged at a current rate of 0.3C until the voltage of the battery cell reached 2.5V, at which time the discharge capacity (C h ).

[0278] The contents of nickel (Ni), cobalt (Co) and manganese (Mn) in the metal elements in the metal composite (unit: mass ppm) are obtained, and the molar ratio of nickel (Ni) in the above three metal elements is obtained from the obtained contents (Ni rt% ).

[0279] The discharge capacity relative to the molar ratio of nickel is defined as the discharge capacity (C h ) divided by the molar ratio of nickel (Ni) obtained as described above (Ni rt% ) value (C h / Ni rt% ) to obtain.

[0280] 3. Capacity retention rate

[0281] The capacity retention ratio is obtained as L of CR according to the following formula: R .

[0282] [Formula CR]

[0283] L R =L2 / L1×100(%)

[0284] In the formula CR, L1 is the discharge capacity of the battery cell in the first cycle under the condition of maintaining 45°C, and L2 is the discharge capacity of the battery cell in the 500th cycle under the condition of maintaining 45°C, wherein 1 cycle is defined as charging to 4.2V at 45°C with a current of 0.5C and a CC-CV charging mode, and then discharging to 2.5V at a current of 0.5C after 0.05C.

[0285] 4. Gas production

[0286] The total amount of gas generated by the battery cells was measured when they were charged and discharged for 500 cycles at 45°C. One cycle was defined as charging to 4.2V at 0.5C and CC-CV charging mode at 45°C, and then discharging to 2.5V at 0.5C after 0.05C.

[0287] The measured physical properties of the metal composites 10 prepared in Examples 1 to 18, Comparative Examples 1 and 2, and the battery cells including the metal composites 10 prepared respectively are described in Table 1 below. In Table 1 below, R A As defined in the following formula A, R B As defined in Formula B below, R C As defined in Formula C below.

[0288] [Formula A]

[0289] R A =W Co / W M1

[0290] In formula A, W Co is the weight % of cobalt relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

[0291] [Formula B]

[0292] R B =W Mn / W M1

[0293] In formula B, W Mn is the weight % of manganese relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

[0294] [Formula C]

[0295] R C =W Ni / W M1

[0296] In formula C, W Ni is the weight % of nickel relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

[0297] In addition, in Table 1 below, C h / Ni rt% It refers to the discharge capacity expressed in molar percentage relative to nickel, L R As defined by the following formula CR.

[0298] [Formula CR]

[0299] L R =L2 / L1×100(%)

[0300] In the formula CR, L1 is the discharge capacity of the battery cell in the first cycle under the condition of maintaining 45°C, and L2 is the discharge capacity of the battery cell in the 500th cycle under the condition of maintaining 45°C, wherein 1 cycle is defined as charging to 4.2V at 45°C with a current of 0.5C and a CC-CV charging mode, and then discharging to 2.5V at a current of 0.5C after 0.05C.

[0301] [Table 1]

[0302]

[0303] Referring to Table 1, Examples 1 to 18 have R within the specified range. A , R B and R C . Therefore, Examples 1 to 18 show excellent discharge capacity, and also show excellent structural stability and life retention rate even in a high temperature environment. Comparative Examples 1 and 2 show a case where the heating rate from room temperature to the calcination temperature in the calcination step (calcination step) is set to a relatively high heating rate. Referring to Table 1, Comparative Examples 1 and 2 have R within the specified range. A , R B and R C Therefore, in Comparative Examples 1 and 2, the discharge capacity is low relative to the content of nickel (Ni), and in particular, Comparative Example 1 has a problem of a large amount of gas generation.

[0304] [Explanation of Reference Numerals]

[0305] 1: Battery cell

[0306] 2: Battery module

[0307] 3: Battery Pack

[0308] 10: Metal composites

[0309] 11: Lithium compound particles

[0310] 12: Extragranular area

Claims

1. A positive electrode active material, comprising a metal composite containing lithium compound particles represented by the following structural formula 1, According to the following formula A, R A In the range of 2 and above to 30 and below: [Structural Formula 1] Li x Ni a Co b Mn c M 1 d M 2 e O 2+y In structural formula 1, 0.95≤x≤1.10, 0.75≤a≤1, 0 <b≤0.2,0<c≤0.2,0<d≤0.15,0<e≤0.1,-0.5≤y≤0.1,M 1 It is the first metal element, M 2 is a second metal element, wherein the first metal element includes one or more selected from Al, Ti, Zr, Sb and Nb, and the second metal element includes one or more selected from Sr, Mg, Ba, Y and Ce, [Formula A] R A =W Co / W M1 In formula A, W Co is the weight % of cobalt relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

2. The positive electrode active material according to claim 1, wherein According to the following formula B, R B In the range of 1 above to 20 below: [Formula B] R B =W Mn / W M1 In formula B, W Mn is the weight % of manganese relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

3. The positive electrode active material according to claim 1, wherein According to the following formula C R C In the range of 30+ to 500+: [Formula C] R C =W Ni / W M1 In formula C, W Ni is the weight % of nickel relative to the total weight of the metal composite, W M1 is the weight % of the first metal element relative to the total weight of the metal composite.

4. The positive electrode active material according to claim 1, wherein The metal composite includes an extra-particle region including one or more selected from oxides, sulfides, oxysulfides, oxyfluorides, and hydrates of a first metal element.

5. The positive electrode active material according to claim 1, wherein The lithium compound particles include the first metal element in a range of 0.001 to 0.1 mole relative to 1 mole of total lithium elements.

6. The positive electrode active material according to claim 1, wherein The lithium compound particles include the second metal element in a range of 0.0001 to 0.05 moles relative to 1 mole of total lithium elements.

7. The positive electrode active material according to claim 1, wherein The first metal element in the lithium compound particles includes Al, and further includes one or more selected from the group consisting of Ti, Zr, Sb, and Nb.

8. The positive electrode active material according to claim 7, wherein According to the following formula P R P In the range 0.1 to 10000: [Formula P] R P =N Al / N M1 In formula P, N Al is the mole % of Al relative to the total moles of the metal composite, N M1 is the total mole % of Ti, Zr, Sb and Nb relative to the total moles of the metal composite.

9. The positive electrode active material according to claim 7, wherein The first metal element in the lithium compound particles includes Al and Ti, according to the following formula Q: Q In the range 1000 to 10000: [Formula Q] R Q =N Al / N Ti In formula Q, N Al is the mole % of Al relative to the total moles of the metal composite, N Ti is the mole % of Ti relative to the total moles of the metal composite.

10. The positive electrode active material according to claim 7, wherein The first metal element in the lithium compound particles includes Al and Zr, according to the following formula R R In the range of 0.1 to 50: [Formula R] R R =N Al / N Zr In formula R, N Al is the mole % of Al relative to the total moles of the metal composite, N Zr is the mole % of Zr relative to the total moles of the metal composite.

11. The positive electrode active material according to claim 7, wherein The first metal element in the lithium compound particles includes Al and Sb, according to the following formula: S On a scale of 1 to 100: [Formula S] R S =N Al / N Sb In formula S, N Al is the mole % of Al relative to the total moles of the metal composite, N Sb is the mole % of Sb relative to the total moles of the metal composite.

12. The positive electrode active material according to claim 7, wherein The first metal element in the lithium compound particles includes Al and Nb, according to the following formula T R T On a scale of 1 to 50: [Formula T] R T =N Al / N Nb In formula T, N Al is the mole % of Al relative to the total moles of the metal composite, N Nb is the mole % of Nb relative to the total moles of the metal composite.

13. A battery cell, comprising an electrode assembly and an electrolyte, The electrode assembly includes a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode. The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material according to claim 1 .